Debating human rights : critical essays from the United States and Asia - Van Ness, Peter; Aziz, Nikhil (Asia's transformations., 1999)
Human rights debates can provoke strong reactions, particularly among people of different cultural backgrounds. The debate over Asian values and the use of human rights diplomacy are the most obvious manifestations of divisions between Asia and the West and reflect particular world views and historical legacies.In this new book, scholars from the United States and several Asian countries debate fundamental issues such as 'Asian values', 'peaceful evolution' and cultural imperialism. Provocative and challenging essays analyse the debate between East and West, presenting critical perspective.